1. Simplify the following expression: 35 + (–13) + (+8) – (–6).
A. 36
B. 50
C. 44
D. 24

Question

Asked 9/19/2012 11:51:41 AM

Updated 6/19/2014 6:40:47 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jerry06 [6/19/2014 6:40:47 PM]

s

Farley44|Points 352|

Question

Asked 9/19/2012 11:51:41 AM

Updated 6/19/2014 6:40:47 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jerry06 [6/19/2014 6:40:47 PM]

Rating

8

35 + (–13) + (+8) – (–6) = 35 - 13 + 8 + 6 = 36

Added 6/19/2014 6:40:45 PM

This answer has been confirmed as correct and helpful.

Confirmed by debnjerry [6/19/2014 7:02:40 PM]

15. What is 23 squared?
A. 1,058
B. 46
C. 529
D. 129 **Weegy:** 23 squared is 529. (More)

Question

Updated 4/1/2014 5:12:53 AM

6 Answers/Comments

3. Simplify this expression: 13 + (–12) – (–5) = ?
A. –6
B. –30
C. 30
D. 6 **Weegy:** The answer is 13 + (–12) – (–5) = 6. (More)

Question

Expert Answered

Asked 9/19/2012 11:53:04 AM

0 Answers/Comments

13. If 3 times a number minus 2 equals 13, what is the number?
A. 5
B. –6
C. 2
D. 4 **Weegy:** A. 5 (More)

Question

Expert Answered

Updated 66 days ago|9/29/2020 12:55:39 AM

1 Answer/Comment

If 3 times a number minus 2 equals 13, 5 is the number.

Solution:

3n -2 = 13

3n = 13 + 2

3n = 15

3n/3 = 15/3

n = 5

Solution:

3n -2 = 13

3n = 13 + 2

3n = 15

3n/3 = 15/3

n = 5

Added 66 days ago|9/29/2020 12:55:39 AM

This answer has been confirmed as correct and helpful.

Solve this equation: –9h – 6 + 12h + 40 = 22.
A. h = – 4
B. h = 4
C. h = –4/7
D. h = 24 **Weegy:** –9h – 6 + 12h + 40 = 22;
3h + 34 = 22;
3h = 22 - 34;
3h = -12;
h = -12/3;
h = -4 (More)

Question

Expert Answered

Updated 8/11/2015 4:12:27 PM

0 Answers/Comments

32,793,330

questions answered

There are no comments.